Beneficial Effects of Glycyrrhizin in Chronic Periodontitis Through the Inhibition of Inflammatory Response - Yaru Sun (Dose-Response, 2020)
Elevated inflammatory cytokines and high mobility group box 1 (HMGB1) production are associated with chronic periodontitis (CP). Glycyrrhizin is the major constituent of Glycyrrhiza glabra. L. (Fabaceae) root with anti-inflammation activities. This study evaluated the effects of glycyrrhizin on CP. TNF-α-treated human periodontal ligament stem cell (hPDLSC) model was established, and was administrated with 1, 2 or 5 mM glycyrrhizin for 24 h. After treatment, the expression of HMGB1and inflammatory cytokines was monitored. Significantly increased HMGB1 (median: 5646.4, range: 1918.2-8233.7 vs median: 204.5, range: 98.7-283.6, pg/mL), TNF-α (median: 345.5, range: 161.0-567.9 vs median: 93.5, range: 58.1-159.3, pg/mL), IL-1β (median: 2014.6, range: 209.5-4308.1 vs median: 224.5, range: 48.8-335.8, pg/mL) and IL-6 (median: 1223.6, range: 398.2-2183.8 vs median: 240.4, range: 105.2-400.5, pg/mL) were detected in gingival crevicular fluid from CP patients. Glycyrrhizin significantly prevented TNF-α-induced expression of HMGB1 (691.5 ± 136.4 vs 142.8 ± 57.3 pg/mL), IL-6 (388.1 ± 85.2 vs 189.4 ± 61.2 pg/mL) and IL-1β (176.3 ± 47.2 vs 53.9 ± 25.7 pg/mL) in hPDLSC. In CP rats, glycyrrhizin significantly decreased HMGB1 (5795.6 ± 1121.5 vs 586.4 ± 436.8 pg/mL), TNF-α (421.8 ± 93.7 vs 87.9 ± 21.6 pg/mL), IL-6 (1423.8 ± 235.2 vs 622.6 ± 176.1 pg/mL) and IL-1β (1562.8 ± 334.3 vs 733.5 ± 265.1 pg/mL) in gingival crevicular fluid. Glycyrrhizin suppresses inflammatory activities in CP rats and represents a promising molecule for controlling CP.